SUFISTIC CHARACTER EDUCATION ON ENRHIRIDON STUDIOSII OF AZZARNUJI - Khalid Ramdhani (Magister PAI Universitas Singaperbangsa Karawang, 2021)
Along with world development civilization on science and technology. The realm of education today seems to be a highlight major public in the sight of social, political, economic and cultural. All dimensions of life seems cynical to the world of education in this globalization era. Starting from the intellectual circle filled with the their rhetoric of the theory of scientific concepts to lay people who do not recognize the bench of studies who speaks with scathing criticism in the rules of education which always changing in according with the demands of the times. But in the middle the rapid development of every aspect of life, felt by the teachers and community widely, as if there is something decreased even almost vanished in a seeker of knowledge (student). The condition of the decline of morality of a student in this generation is getting down dramatically compared with those of previous generations.We need to find an effective and efficient solution in this condition, so that moral decadence does not continue to occur. Education is not only in science and skill oriented but also must keeping the best of values life. If the government with the slogans